Association of Betatrophin, TNF-? and IL-6 with diabetic microvascular and macrovascular complications - Gozel, Nevzat; Melek, Elif; Yakar, Burkay; Önalan, Erhan; Gursu, M.ferit (My University, 2020)
Aim: The most important goal in the treatment of Diabetes Mellitus is to protect patients from micro and macro complications.Inflammatory cytokines and betatrophin have been reported to play a role in diabetic micro and macro complications. This studyaimed to investigate the effect of serum Betatrophin, TNF-? and IL-6 levels on diabetic micro and macro complications in patientswith type 2 Diabetes Mellitus.Materials and Methods: This case-control study was conducted with 91 type 2 Diabetes Mellitus (T2DM) patients betweenJanuary-December 2018. Case series with 91 patients divided into three groups were included; 31 T2DM patients without diabeticcomplications (group 1=control), 30 patients with diabetic microvascular complications (group 2) and 30 patients with diabeticmacrovasculer complications (group 3). Blood was collected to evaluate biochemical parameters, TNF-?, IL-6 and betatrophin.Results: Betatrophin level was high in patients with renitopathy (p=0.042) and diabetic foot (p=0.036). TNF-? levels were higherin patients with both microvascular and macrovascular complications compared to the control group (p<0.001). IL-6 levels wereincreased only in the group with macrovascular complications (p=0.027).Conclusion: Betatrophin, TNF-? and IL-6 were associated with diabetic complications. Larger studies are warranted to establish thereal impact of this finding.
Keywords: Genel ve Dahili Tıp